Story solutions using tales to build character and teach bully prevention, drug prevention, and conflict resolution - Strauss, Kevin 1969- (Libraries Unlimited, 2011)
This book contains "background information, traditional stories, and skill-building activities that will enable librarians and other educators to help their students master bullying and drug prevention, self-control, and conflict resolution, as well as establish health self-esteem and optimism."--Back cover.